PERAN ORANG TUA DALAM MENERAPKAN PENDIDIKAN AGAMA ISLAM DI KELUARGA - Akbar, M. Rafli Fakhrul; Hilmi, Irpan; Anwar, Asep Hermawan (Prodi PAI IAILM Suryalaya, 2022)
Parents as natural educators play an important role in educating children, especially in implementing Islamic religious education in the family. Teach, assess, evaluate and provide motivation so that children can achieve what is expected, and even become role models for children. This study aims to find out how the role of parents in the family, the difficulties of parents in educating children and how to overcome them, and how the role of parents in implementing Islamic Religious Education in the family. The location of this research is in RT 02 Kampung Panulisan Desa Kurniabakti Kecamatan Ciawi Kabupaten Tasikmalaya. The findings in this study are that the role of parents in implementing Islamic religious education in the family is not easy. Parents should pay attention to their children's religious education, for example getting used to the evening readings, learning to pray in congregation for boys, instilling religious values. So that in the future children will be equipped with strong faith, become a useful generation, and be able to face daily problems related to religion.